Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852